Peranan Intelijen Kejaksaan Tinggi Riau dalam Pengungkapan Dugaan Tindak Pidana Korupsi Oleh : Saidil Adri Pembimbing I : Dr. Erdianto Effendi, SH.,M.Hum Pembimbing II : Ferawati, SH., M.H Alamat: Jalan Kembang Harapan, Gang Seliangguri, Pekanbaru-Riau Email: saidiladri01@gmail.com - Saidil Adri; Erdianto Effendi; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
One of the crimes that can be said to be unsettling and quite phenomenal is the problem of corruption. This criminal act not only harms the state's finances, but also violates the social and economic rights of the people. Corruption is a serious problem, this crime can endanger the stability and security of society, endangering socio-economic development and also politics, and can damage the values of democracy and morality because gradually this act seems to be a culture. The AGO is an institution authorized in the criminal act of corruption. The purpose of this thesis is to know the role of the High Intelligence of Riau Intelligence in Disclosure of Alleged Crime of Corruption and Barriers faced by the High Prosecutor's Office of Riau in Disclosure of Alleged Corruption.This research is sociological or empirical research that is kind of research which use society assumption in searching facts that happened in field to answer an existing problem. The research was conducted in the jurisdiction of the Riau High Prosecutor's Office. While the population and sample are the parties related to the problems studied in this study, the data sources used, primary data, secondary data, and tertiary data. Technique of collecting data in this research by interview and literature study.From the results of research that the authors do can be concluded, first The role of Intelligence of the Riau High Prosecutor Office in the disclosure of alleged corruption crime is to conduct activities and operations of judicial intelligence or investigation to collect data or information that can be used as evidence of whether or not there has been a criminal act of corruption which further evidence is submitted to the Leader or parties concerned for further decision making. The obstacles faced by the Riau High Prosecutor's Intelligence in uncovering allegations of corruption in the Riau High Prosecution's legal area are human resources (HR) factors, legal regulatory factors that are perceived to be inconsistent with the demands of the development of society, the difficulty factor for the Intelligence Prosecutors in obtaining evidence in the form of letters, valuable documents, and related assets, the lack of funding factors, lack of coordination by the Prosecutor's Intelligence with the relevant agencies, and the lack of planning factors undertaken by the Riau High Prosecutor's Intelligence.Keywords: Intelligence - Prosecutor - Crime – Corruption.